Interaction Of Training Methods and Explosive Power On Learning Outcomes For Running 100 Meters - Muhammad Ramli Buhari; Muchamad Samsul Huda; Hamdiana Hamdiana; Ruslan Ruslan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the interaction between the training method and the explosive power of the leg muscles on the learning outcomes of the 100 meter run. This research was conducted at the Teaching and Education Faculty of Mulawarman University with an experimental method, with a 2 x 2 factorial design. The sample in this study was 120 students, divided into 4 groups, each group consisting of 30 students. Analysis of the data used is a two-way Analysis of Variance (ANOVA). The results of the study stated that: (1) The acceleration sprint training method and the sprint training method did not have different effects on improving learning outcomes in running 100 meters, Fo = 5.452 > Ft5% db (1;116) = 3.84, (2) Without paying attention to the use of the two forms of training methods (acceleration sprint training method and the sprint training method), the explosive power of the strong leg muscles has a different effect when compared to the explosive power of the weak leg muscles on the learning outcomes of running 100 meters, Fo = 0.237 ? Ft5% db (1;116) = 3.84, (3). There is an interaction between the training method and the explosive power of the leg muscles on the learning outcomes of the 100 meter run, Fo = 13.044 > Ft5% db (1;116) = 3.84.